The Influence of Work-Life Balance and Work Overload on Burnout Levels of Generation Z Employees in Surabaya - Rohmawati, Lindah; Julindrastuti, Dijah (Doctoral Program of Social Science Pasundan University, 2025)
This study aims to analyze the effect of work-life balance and work overload on burnout levels in Generation Z employees in Surabaya. Generation Z is known as a group of workers who prioritize balance between work and personal life, but are also vulnerable to excessive work pressure. This study uses a quantitative method with data collection techniques through questionnaires distributed to 100 Generation Z employees in various industrial sectors in Surabaya. The sampling technique used is purposive sampling, with the criteria for respondents being employees aged 18–27 years, employees working in Surabaya, and employees who have been working for at least 1 year. The data obtained were analyzed using multiple linear regression techniques to test the relationship between the independent variables (work-life balance and work overload) with the dependent variable (burnout). The results showed that work-life balance has a significant negative effect on burnout, meaning that the better the balance between work and personal life, the lower the burnout level. Conversely, work overload has a positive and significant effect on burnout, indicating that the higher the workload, the higher the burnout level experienced by Generation Z employees